Exploratory data analysis of measles transmission among children aged 0-4 years - Naila Nur Ramadani; Hendra Dhermawan Sitanggang; Rd Halim; Muhammad Syukri (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Measles is a highly contagious disease that primarily affects children, particularly those aged 1–4 years, who account for the highest proportion of cases both nationally and in Jambi Province. The decline in routine immunization coverage during and after the COVID-19 pandemic has widened the immunity gap, triggering a surge in measles cases across Indonesia, including Jambi Province, where the incidence rate of suspected measles rose sharply from 0.55 per 100,000 population in 2021 to 25.05 per 100,000 in 2023, leading to outbreaks in 2022 and 2023. However, epidemiological research using individual-level surveillance data remains limited in Jambi Province. Purpose: To analyze Exploratory Data on Measles Transmission in Children Aged 0-4 Years. Method: This analytical descriptive research applied the Exploratory Data Analysis (EDA) approach using RStudio software. Secondary data is sourced from the Jambi Provincial Health Office's Measles-Rubella Case Tracking Individual Report Form (MR02). From an initial population of 456 suspected children aged 0-4 years, final samples were obtained from 332 cases that met the inclusion criteria (96 confirmed positive/equivocal cases of measles IgM and 236 negative cases). Analysis and visualization of the place was carried out up to the sub-district level. Results: The incidence rate of measles under five years jumped sharply from 0.64 per 100,000 population (2021) to a peak of 12.50 per 100,000 population (2023), before finally declining in 2024–2025. Confirmed cases are dominated by the age group of 36-59 months (43.8%) and children with unvaccinated status (56.2%). The age group of 24-35 months is the age group that dominates the immunization status who are not immunized with a proportion of 76.5% of children. Measles cases are distributed almost throughout Jambi Province with the highest case burden in Jambi City (Kota Baru and Lake Sipin Districts), Sarolangun Regency (Pelawan District), and Tebo Regency (Rimbo Bujang, Sumay, and Central Tebo Regencies), which is directly proportional to the low local second dose immunization coverage (MR2). Time-based analysis shows a fluctuating pattern of local transmission and there is a tendency for cases to increase in August-October. Excellent specimen condition (97.9% good condition), but experiencing extreme administrative and diagnostic delays (Turnaround Time / TAT) with the highest median reaching 101 days in 2023. Conclusion: The incidence of measles in toddlers aged 0-4 years in Jambi Province for the 2021-2025 period shows an uneven distribution according to people, places, and times. The age group of 36-59 months and cases with no immunization history are the most affected groups, with the concentration of cases in Jambi City, Tebo Regency, and Sarolangun Regency. The increase in incidence in 2023 and the still low coverage of MR2 immunization in several risk areas, accompanied by laboratory turnaround time that has not met standards, shows the need to strengthen the immunization program and measles surveillance system.